Success implementation of online technology information system on market cooperative kumbasari denpasar - Yadnya, Putu; Suprasto, Herkulanus Bambang; Dwirandra, Anak Agung Ngurah Bagus; Suaryana, I Gusti Ngurah Agung (International research journal of management, IT and social sciences, 2019)
The research was intended at identifying the contribution of system quality influences toward use and user satisfaction. The primary data in the current was obtained directly from the questionnaire. The method used to obtain data was non-participant observation using a questionnaire. The list of structured questions asked to field officers and back-officers and unit managers in the market cooperative Kumbasari Denpasar. It was conducted in all market cooperative service units of Kumbasari Denpasar. There were 14 units located in traditional markets in Denpasar, Gianyar, and Badung. The study result showed system quality influences towards use of online-based cooperative information system. It was due to the system users believe the reliability of the system used in performing daily tasks. The running system was able to answer the needs of users of online-based cooperative information system. The system quality influences user satisfaction towards online cooperative information system. The reliability of the information system was built also influences the level of user satisfaction system. It was due to the most user of information system believe and feel the system can facilitate their work. Therefore, they can easily do relying their work on existing information systems.